EPPS Test Application Development for Selecting Students to Participate in Cooperative Program on Small and Medium Enterprise - Tan Amelia; Tri Sagirani; Rr. Dewintha Indriyanti (International Journal of Informatics and Communication Technology (IJ-ICT), 2014)
Cooperative Education (CO-OP) is a program that aims to sharpen its participants’ entrepreneurship action and spirit. In order to select the students to participate in this program, STMIK STIKOM of Surabaya uses EPPS psychological test which can measure the achievement, deference, autonomy, affiliation, nurturance, and endurance of CO-OP participant. The used of EPPS psychological test is based on the reason that this test is one of the personality tests prepared to measure the power of someone’s need. By the existence of EPS application in selecting CO-OP participant, a proper result’s validity is expected to be reached.